SPECIES COMPOSITION OF REPTILES IN DA HUOAI DISTRICT, DI LINH PLATEAU, LAM DONG PROVINCE - Thi Thuy Duong, Le; Gia Thinh, Tran (Journal of Forestry Science and Technology, 2023)
Lam Dong province is home to a highly diverse reptilian fauna that is under increasing threat by ongoing habitat loss and modification. Since 2011, there have been seven new reptilian species discovered in Lam Dong province indicating that the knowledge of reptilian diversity in the area is still incomplete. In July and August 2020, we conducted two short field trips to survey reptiles in Da Huoai district, Di Linh plateau, Southern Lam Dong province. According to morphological comparisons, we firstly reported the list of 14 reptile species from this area including five lizard species and nine snake species. Two species Coelognathus flavolineatus and Pareas temporalis are reported from Lam Dong province for the first time. Among recorded reptile species, there are one endemic species to Vietnam (Pareas temporalis) and two vulnerable species (Physignathus cocincinus and Trimeresurus rubeus) according to the IUCN Red List (2022). Our new records bring the total number of reptilian species in Lam Dong province to 99 species with four turtle species, 57 snake species, and 38 lizard species. Due to the reptile faunal differences and the expansion of cash crops, the construction of roads, houses, and associated infrastructure, further surveys for the possible existence of other reptilian species in the Di Linh plateau are suggested.